KAJIAN EKSEGETIKAL MAKNA IMAN BERDASARKAN SURAT IBRANI 11:1-3 - Waharman Waharman (Sekolah Tinggi Teologi Arastamar Bengkulu, 2016)
The Hebrews were written to strengthen their faith in Christ by carefully explaining the superiority and firmness of God's revelation and redemption in Jesus Christ. He showed that the provision of redemption under the old covenant had been fulfilled and was no longer used because Jesus had come and established a new covenant by His death-working peace. The author also calls on all believers to maintain recognition of Christ so that at the end, the author then advises him to move forward toward spiritual maturity, and to not return to life under penalty by renouncing trust in Jesus Christ. In this study of Hebrews 11: 1-3, the writer provides understanding and understanding, as well as giving advice that faith is the basis for every believer, as well as a certain hope for Jesus Christ. As a result of the church's lack of understanding of the meaning of faith, many apostate congregations who abandoned their faith, beliefs, and perseverance before God disappeared. besides that most of the congregation have experienced the decline of faith. Therefore believers need to understand the text of God's Word from Hebrews 11: 1-3 in every step of life.